Sistem Monitoring Perilaku Pengendara Mobil Berbasis Internet of Things - Rahayu, Andri Ulus (Universitas Andalas, 2021)
This research is created as a system for a car rental service. The system has monitoring features allowing the car rental owner to monitor the engine condition. The monitoring is performed by using a web interface that could read data from OBD-II that sent by raspberry pi 2. The owner can also monitor the position of the car by using coordinates sent from a smartphone by utilizing the GPS feature. In addition, it also has a reporting feature that allows the owner to track the data history from OBD II about the engine rpm, speed, engine load & temperature. Moreover, the owners can identify the route that has been passed by their car. Likewise, this system provides a program that analyzes the car driver's behavior based on the determined rules. The analysis was conducted based on all data from OBD-II in the database server and all data of driving rules violation performed by the driver. The result is an assessment of the driver as a driving error rate. This study generated 173 data of which 9 were driving rules violations with a 5.20% driving error rate. The report can be obtained by selecting the time interval. It also downloadable and can be sent by e-mail.